Program impact and potential pitfalls of multi-purpose technologies (MPTs) for HIV prevention and contraception - Latka, Mary H.; Vahle, Kristin; Li, Kevin; Gomes, Megan; Dam, Anita (Frontiers in Reproductive Health, 2023)
The overlapping epidemics of HIV and unplanned pregnancy disproportionately affect adolescent girls and young women (AGYW) in sub-Saharan Africa. Prevailing dynamics driving benefits of any prevention method at the population level depend on: 1) population size, risk profile, and prevalence of method use, 2) method efficacy, and 3) method use-effectiveness. Adding a multi-purpose technology (MPT) to prevent HIV and pregnancy to this three-part equation results in scenarios that may enhance HIV population impact, even with methods that exhibit less than “perfect” method efficacy, by extending protection among existing users and attracting new users, resulting in greater population coverage. However, the interplay of epidemic drivers is complex and the greatest population benefit of such a MPT would be realized among those most at risk for HIV and pregnancy, and could be harmful if successful contraceptive users switch to a method with lower use–effectiveness. While MPTs are highly desired, and may offer considerable individual, population, and system-level public health benefits, there is no “magic bullet”, nor single prevention method–MPT or otherwise–that will end the HIV epidemic nor fully resolve unmet need for family planning. All methods have inherent tradeoffs and women have varied reproductive and HIV prevention needs across their life course. Key programmatic features to maximize the potential of MPTs include offering them among a range of safe and effective methods with comprehensive information about their features allowing women to make a fully-informed method choice. Programmatic follow-up should support consistent and correct use to maximize use-effectiveness, and then monitor for potential untoward effects.